2012
DOI: 10.1177/1538574411434164
|View full text |Cite
|
Sign up to set email alerts
|

Supraclavicular Scalenectomy for Thoracic Outlet Syndrome—Functional Outcomes Assessed Using the DASH Scoring System

Abstract: This study reconfirmed the value of supraclavicular approach for TOS, with the vast majority reporting subjective improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Several other studies have reported DASH scores after surgical treatment for TOS ranging from 3.5 to 36 [ 11 , 12 , 13 , 14 , 15 , 16 ]. Functional outcome as reported by DASH scores is better in athletes [ 11 ] and in vascular forms of TOS [ 14 , 16 ]. The explanation for the differences in the outcome between vascular forms of TOS and NTOS is that a substantial number of patients with VTOS or ATOS also undergo revascularization procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have reported DASH scores after surgical treatment for TOS ranging from 3.5 to 36 [ 11 , 12 , 13 , 14 , 15 , 16 ]. Functional outcome as reported by DASH scores is better in athletes [ 11 ] and in vascular forms of TOS [ 14 , 16 ]. The explanation for the differences in the outcome between vascular forms of TOS and NTOS is that a substantial number of patients with VTOS or ATOS also undergo revascularization procedures.…”
Section: Discussionmentioning
confidence: 99%
“…11,12) All surgical decompressions in our study included scalenectomy for all of the cases, cervical rib excision in 85%, and 1st rib removal in 30% through the supraclavicular approach, which provides good visualization of the thoracic outlet area and excellent exposure for arterial reconstruction if needed and has been shown to have excellent results in many series. [13][14][15][16][17] Only five cases of venous TOS were treated in this series, in which 2 of them presented with acute primary DVT, which had a lower incidence than expected for a vascular TOS since venous cases are more common. 1) The lower number of…”
Section: Disclosure Statementmentioning
confidence: 88%
“…In addition, to evaluate these patients, the standard care level of the patients with thoracic outlet syndrome affiliated to the Rehabilitation Department of The Brighten and Women's Hospital in 2007 has recommended three general measuring scales, including shoulder pain and disability index (SPADI), simple shoulder test (SST), and American shoulder and elbow surgeons (ASES). Moreover, the "arm, shoulder, and hand" questionnaire has been used in some studies conducted on the patients with thoracic outlet syndrome [20][21][22]. In Table 1, the characteristics of the resources and in Table 2, two characteristics on evaluating the treatment outcomes [23][24][25][26] are presented.…”
Section: Resultsmentioning
confidence: 99%